EFFECT OF MEDICAL EDUCATION ON THE MORAL COMPETENCE OF MEDICAL STUDENTS (Proceeding of the International Conference on Arts and Humanities, 2019)
The aim of the present study is to investigate the effect of medical education on moral competence of medical students. It is hypothesized that there will be a significant effect of medical education on moral competence of medical students. 200 (N) students chosen for this study are first and final year Bachelors of Medicine, Bachelors of Surgery (MBBS) from public and private medical universities of Karachi, Pakistan.Moral Competence test by Lind (2015) is used to measure the C Score. Through statistical analysis of the data, it is found statistically significant (p
Keywords: moral competence; medical education